FUNCTIONAL ANALYSIS OF BRACON HEBETOR VENOM ON TARGET AND NON-TARGET INSECT CELL LINES (Acta Entomologica Serbica, 2017)
Insect cell cultures are widely used in studies of insect cell physiology, toxicology, developmental biology and microbial pathology. The lethal effects of crude venom extracted from the ectoparasitic wasp Bracon hebetor were examined with three cultured insect cell lines; Spodoptera frugiperda (Sf9), Tribolium castaneum (TcA) and Aedes aegypti (Aag-2). Venom caused cells to round-up, swell and eventually die. Despite similar sensitivities and overlapping LC50 values [(0.00125-0.00695) venom reservoir equivalents (VRE)/µl], significant differences were noted at the onset of cytotoxicity among the three insect cell lines. Cells from the Tribolium castaneum (TcA) and Aedes aegypti (Aag-2) showed little sensitivity to the venom: 0.0046 VRE were needed to induce 50% mortality in TcA [50% lethal concentration (LC50) = 0.0046 VRE/µl], and 0.0069 VRE were needed to induce 50% mortality in Aag-2 [50% lethal concentration (LC50) = 0.0069 VRE/µl). Over 80% of the Sf9 cells were nonviable within 1 h after the addition of an LC99 dose of venom, whereas the other cells required a 5-10-fold longer incubation period to produce mortality above 50%.